2019
DOI: 10.3390/ijerph16081470
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle Disorders in Professional Female Rhythmic Gymnasts

Abstract: The aim of this research was to compare menstrual cycles, menstrual disorders, and the prevalence of premenstrual syndrome (PMS)and premenstrual dysphoric disorder (PMDD) in professional female gymnasts and their peers who donot practice any sport, and to identify factors causing a predisposition to premenstrual tension syndrome and premenstrual dysphoric disorders in both groups. The prospective study involved apopulation of 85 girls. The study group consisted of 45 professional female gymnasts (15–17 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 21 publications
(32 reference statements)
4
17
0
2
Order By: Relevance
“…According to the other study, however, caffeine and alcohol intake was significantly correlated with the incidence of premenstrual symptoms (PMS, PMDD) among elite gymnasts 12 . Other previous studies have shown that alcohol consumption after menstruation was significantly associated with the development of PMS…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…According to the other study, however, caffeine and alcohol intake was significantly correlated with the incidence of premenstrual symptoms (PMS, PMDD) among elite gymnasts 12 . Other previous studies have shown that alcohol consumption after menstruation was significantly associated with the development of PMS…”
mentioning
confidence: 74%
“…In a study of medium to long-distance female athletes in Poland, . In a study of 52 Brazilian female football players, 59.6% of athletes had PMS 11 , and in a study of 45 Polish female gymnasts, 48.89% of athletes were shown to have PMS 12 . The reported prevalence of PMS varies according to the study subjects.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Sebagian besar penelitian yang dilakukan untuk mengetahui hubungan aktivitas fisik dengan munculnya sindrom pra-menstruasi menunjukkan bahwa aktivitas fisik merupakan faktor protektif terhadap terjadinya sindrom pra-menstruasi. Namun demikian, ditemukan penelitian yang menunjukkan hasil yang bertolak belakang, bahwa aktivitas fisik memicu terjadinya sindrom pramenstruasi (11). Pada penelitian tersebut, dijelaskan bahwa aktivitas fisik yang dimaksud meliputi aktivitas olahraga kompetitif.…”
Section: Pembahasanunclassified
“…This phenomenon is also accentuated by the role that makes the aesthetic component in this discipline [7]. Menarche's delay and eating disorders are common in gymnasts, which are considered a high-risk group of malnutrition [8,9].…”
Section: Introduction mentioning
confidence: 99%